Topological Insulator: <tex Notation="TeX">$\hbox{Bi}_{2}\hbox{Te}_{3}$ </tex> Saturable Absorber for the Passive Q-Switching Operation of an in-Band Pumped 1645-nm Er:YAG Ceramic Laser - Pinghua Tang; Xiaoqi Zhang; Chujun Zhao; Yong Wang; Han Zhang; Deyuan Shen; Shuangchun Wen; Dingyuan Tang; Dianyuan Fan (IEEE Photonics Journal, 2013)
An in-band pumped 1.645-μm Er:YAG ceramic laser passively Q-switched by a topological insulator: Bi2Te3 saturable absorber is reported. The average output power could reach up to 210 mW, corresponding to a pulsewidth, a pulse repetition rate, and a per-pulse energy of 6.3 μs, 40.7 kHz, and 5.3 μJ, respectively. This result indicates that the topological insulator: Bi2Te3 could be a promising saturable absorber such as graphene, with potential applications for solid-state lasers.